Reason, Justification, and Contractualism Themes from Scanlon - Forst, Rainer; Frauchiger, Michael; Mantel, Susanne; Nagel, Thomas; Olsaretti, Serena; Parfit, Derek; Scanlon, T. M.; Stemplowska, Zofia; Stepanians, Markus; Stepanians, Markus (Lauener library of analytical philosophy ;, 2021)
This book collects major original essays developed from lectures given at the award of the Lauener Prize 2016 to T. M. Scanlon for his outstanding oeuvre in Analytical philosophy. In "Contractualism and Justification," Scanlon identifies some difficulties in his theory and explores possible ways to deal with them. In "Improving Scanlon's Contractualism," D. Parfit recommends revisions and extensions of Scanlon's theory, while R. Forst suggests in "Justification Fundamentalism" that Scanlon may want to replace reason with justification as his foundational concept. T. Nagel raises fundamental questions concerning "Moral Reality and Moral Progress," and S. Mantel offers in "On How to Explain Rational Motivation" a critical discussion of Scanlon's cognitivist theory of motivation. Z. Stemplowska does the same for Scanlon's conception of responsibility in "Substantive Responsibility and the Causal Thesis," and S. Olsaretti suggests in "Equality of Opportunity and Justified Inequalities" an alternative to Scanlon's arguments against economic inequalities. All contributors receive extensive replies by Scanlon. For anyone interested in Scanlon's seminal work in moral and political philosophy, the present volume is utterly indispensable.